Analysis of Learning Models in Secondary Schools to Improve the Quality of Student Education - Suwandi; Putri, Riska; Utaminingsih, Sri (Academy of Social Science and Global Citizenship Journal, 2024)
This research examines various learning models implemented in secondary schools in different countries and their impact on the quality of education. In the context of globalization and rapid changes in the world of work, education is expected to develop skills relevant to future challenges. This research analyzes seven main learning models that have been proven effective in various countries, namely competency-based models, project-based learning, flipped classroom, inquiry-based learning, collaborative learning, problem-based learning, and technology-based models. Each model has its own characteristics and advantages, and is applied based on local needs and context. Competency-based models, for example, focus on developing students' practical skills needed in the world of work, while flipped classroom and technology-based models provide flexibility in material delivery and allow for more interactive learning. This study uses a literature study approach to collect data and information related to the implementation of these learning models. The results show that the implementation of the right learning model can improve students' motivation, engagement and learning outcomes. Other important factors are infrastructure readiness, teacher training, and education policy support for learning innovation. In Indonesia, the adaptation of these models can improve the quality of education at the secondary school level, provided that there are supporting policies and training for educators. This research provides recommendations for the development of more innovative and skills-based education policies to prepare young people for global challenges.